Supported playgroups as a setting for promoting physical activity of young children: Findings from a feasibility study in south‐west Sydney, Australia. (23rd December 2013) - Weber, Danielle; Rissel, Chris; Hector, Debra; Wen, Li Ming
<x xml:space="preserve">Abstract</x> Aim This study examined the feasibility of the supported playgroups (SPGs) setting to promote physical activity among young children and increase staff and parental knowledge of the physical activity recommendations for young children. Methods A 10‐week Active Play@Playgroup intervention was conducted with 28 co‐ordinators and 174 parents attending SPGs located in south‐west Sydney. The intervention involved training and providing support to SPG co‐ordinators to help promote active play and reduce screen time for young children. The effectiveness of the intervention was evaluated using pre‐ and post‐intervention surveys. The main outcomes included changes in parents' knowledge of physical activity recommendations for 0‐ to 5‐year‐olds, and children's physical activity and sedentary behaviours outside of playgroup. Results The mean time children spent playing actively outdoors during the week increased (pre: 1.48 h/day vs. post: 1.95 h/day, P = 0.02), and the time parents spent playing actively with their children increased both during weekdays (pre: 1.57 h/day vs. post: 2.42 h/day, P = 0.01) and on the weekend (pre: 2.95 h/day vs. post: 3.83 h/day, P = 0.02). There was also a significant increase in the proportion of parents with correct knowledge of recommended screen time for 0‐ to <2‐year‐olds (pre: 7.9% vs. post: 23.4%, P = 0.02). Conclusions It is feasible and potentially effective to use the SPG setting to promote active play among young children and increase parents' knowledge of physical activity recommendations for young children.